Religion and Economics: Applying Buddhist Economic Principles in Social Economy Enterprises - Ditta Ade Sudarma; Agar Devi Shrestha (Subhasita: Journal of Buddhist and Religious Studies, 2023)
Social Economy EnterprisesThe relationship between religion and economics has always been interconnected. Every religion has its teachings regulating economic life, especially Buddhism. This study explores the application of Buddhist economic principles in social economy enterprises, focusing on the case of Cahaya Dhamma Phala Cooperative in Banjarnegara Regency, Central Java. Employing a qualitative approach, data collection involved observation and interviews. The research reveals a profound connection between Buddhism and economic life, particularly within cooperative activities, guided by the principles of Utthanasampada (full of enthusiasm), Arakha Sampada (guarding and maintaining), Kalyana-mitta (having good friends), and Samma Jivikata (balance). The cooperative's management and members adeptly apply these Buddhist principles, resulting in a harmonious integration of religious and economic pursuits. The study underscores the transformative impact of these principles on achieving balance and sustainability within the Cahaya Dhamma Phala Cooperative, emphasizing the intersection of religion and economics in fostering a socially responsible and prosperous enterprise.